Global research trends in Chinese medicine for the treatment of non-alcoholic fatty liver disease (NAFLD): A bibliometric study - Kangjie li; Jie Wang; Ming Dang; Runxin Ren; Maomao Fu; Jing Wang; Qiao Zhang; Chongbo Zhao (Pharmacological Research - Modern Chinese Medicine)
Abstracts: Background: The global incidence of non-alcoholic fatty liver disease (NAFLD) is rising due to changes in modern lifestyle and dietary habits, making it one of the leading causes of chronic liver disease. NAFLD can progress to more severe liver conditions, imposing significant economic burdens. Currently, no FDA-approved drugs are available for its treatment. However, Traditional Chinese Medicine (TCM) has gained attention for its unique theoretical framework and therapeutic strategies, particularly its potential to improve liver health by modulating liver function. Recent studies have also highlighted TCM's ability to regulate gut microbiota, offering a promising avenue for NAFLD management. To better understand the evolving role of TCM in treating NAFLD, a comprehensive analysis of existing research is necessary. Methods: In this study, the Web of Science database was chosen as the primary data source to investigate the treatment of non-alcoholic fatty liver disease (NAFLD) using traditional Chinese medicine (TCM). Specifically, the search focused on English articles and review articles indexed in the SCI-E and SSCI databases, spanning from January 1, 2012, to October 30, 2024. The search strategy employed the following formula: TS = (“non-alcoholic fatty liver disease” OR “Metabolic dysfunction-associated fatty liver disease” OR “NAFLD”) AND TS = (“TCM” OR “Herbal medicines”). The analysis encompassed various aspects such as authors, keywords, journals, countries, institutions, and references. For this purpose, analytical tools including VOSviewer, Bibliometrix, and CiteSpace were utilized to systematically evaluate the gathered data. Results: A total of 306 documents were retrieved, indicating a rising trend in the number of publications, which is expected to accelerate in the future. China is at the forefront in terms of both the quantity of publications and total citations, demonstrating strong international collaboration. Within China, Shanghai University of TCM and Chengdu University of TCM are leading institutions, having established a stable group of collaborating authors. The top 10 key journals account for 49.02 % of the publications, with Frontiers in Pharmacology being the most prolific, while the World Journal of Gastroenterology boasts the highest average number of citations. The most frequently cited journals are Hepatology, Journal of Hepatology, and Journal of Ethnopharmacology. Keyword analysis reveals that high-frequency terms such as steatohepatitis are prevalent, addressing topics like pathogenesis, indirect therapeutic effects, and molecular biological mechanisms. Recent outbreak word analysis highlights 'cell' and 'steatohepatitis' as current hotspots, with 'NASH' anticipated to be a focal point in 2024. Discussion: The number of publications on TCM treatments for NAFLD has steadily increased, with TCM exhibiting therapeutic effects through various mechanisms, including anti-inflammatory, antioxidant, lipid metabolism modulation, and gut microbiota regulation. The anti-inflammatory effects primarily result from the inhibition of inflammatory signaling pathways. Antioxidant properties arise from bioactive compounds in TCM and their modulation of related pathways. Lipid metabolism improvement occurs through the regulation of spleen and stomach functions, promoting lipolysis. Furthermore, TCM regulates intestinal microbiota, restoring microbial balance and enhancing intestinal barrier function. Future research should focus on the synergistic mechanisms underlying these multiple pathways to develop more comprehensive therapeutic strategies. Additionally, expanding the data sources for further analysis is crucial. However, this study has limitations, including reliance on a limited selection of databases and keywords from Web of Science, which may not capture all relevant literature, and the potential bias in the bibliometric analysis.